Triclosan-coated polyglactin-910 for closure of infected abdominal wall of rats with peritonitis - Tôrres, Juliana Lima; Araújo-Filho, Irami; Araújo, Maria de Lourdes M. de F. N.; Rêgo, Amália Cínthia Meneses; Sá, Marília de vasconcelos; Medeiros, Vítor Brasil; Tôrres, Suzana Lima; Azevedo, Ítalo Medeiros de; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2012)
Purpose: Antibacterial-coated sutures have been reported to reduce the incidence of surgical site infections both in experimental and clinical studies. The aim of the present study was to evaluate the performance of coated polyglactin 910 suture with triclosan (Vicryl Plus) and traditional polyglactin suture (Vicryl) with regard to surgical abdominal wound infections following abdominal sepsis by cecal ligation and puncture. Methods: Twelve Wistar rats weighing 285±15g were randomly distributed on Vicryl plus group (n=6) and Vicryl group (n=6). The variables to be evaluated were: (1) tensile strength of the tissues at the site of the suture (2) the histopathological aspects with counts of inflammatory cells; (3) bacteriology - growth of Gram-positive and Gram-negative bacteria. Results: On the fifth postoperative day bacterial cultures of the secretions collected from abdominal wounds revealed growth of Staphylococcus aureus and Klebsiella sp. A significant difference was observed in the mean colony forming units of Gram-positive and Gram-negative bacteria in wounds sutured with noncoated (Vicryl) versus triclosan-coated sutures (Vicryl Plus). In the Vicryl group, the average tensil strength was 533.8±75.8 gf/mm2, significantly lower than in Vicryl Plus group (854.0±51.7 gf/mm2). Statistical analysis revealed a significant difference (p<0.0001). The density of the inflammatory reaction was significantly higher (p=0.003) in the Vicryl group rats (1033.26±153.97) than the in Vicryl Plus group (723.29±96.5). Conclusion: This study demonstrated the in vivo efficacy of Coated Vicryl Plus suture, that prevented bacterial colonization and reduced the inflammatory response, allowing tissue healing even in infected wounds.